Pola Tanam Polikultur Sayuran pada Pekarangan Sempit Melalui Sistem Vertikal Garden Dalam Mendukung Ketahanan Pangan pada Masa Pandemi Covid-19 - Sri Tirto Madawistama Mada; Khomsatun Ni’mah; Yeni Heryani; Dian Kurniawan (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
The utilization of yardland in each house can be done optimally, especially in terms of realizing family-based food security. Optimal utilization through planting various types of plants, especially vegetable crops, has great potential to fulfill food for the family. Wanasigra Village, Ciamis Regency is one of the areas affected by the covid 19 pandemic, the village is far from markets and cities so it is constrained in terms of food availability, through increasing food security in Wanasigra Village, there is an increase in income and smooth distribution of marketing of processed food and agricultural products so that food security is sustainable. his family's food becomes more controllable. Through the concept of a vegetable polyculture cropping pattern by utilizing a narrow yard through a vertical garden system, the Wanasigra Village community can maintain their family's food security. Through a partnership, the object of the Food Security scheme service is the residents and farmer groups of the Wanasigra village. This community service activity provides guidance to residents and farmer groups in utilizing their home gardens through the Vegetable Polyculture Planting Pattern through the Vertical Garden System. The harvests of residents and farmer groups can be consumed by their families or can also be sold. Sales are facilitated by a chairman who is appointed to distribute to other areas outside the Wanasigra village. The results of the assistance and development of the residents and farmer groups of the Wanasigra village are seen to be more independent in food availability and obtain additional income for their families so that it can be said that they have been able to maintain food security for the long term. The method used in the service is through counseling, discussion, assistance, and the introduction of technology to marketing through agricultural experts appointed by external parties.